Migration and the Local Transformation of Overseas Development Aid: an Analysis of Migrants' Access to ODA Funds in Catalonia. Issue 4 (1st June 2015) - Østergaard‐Nielsen, Eva; Acebillo‐Baqué, Míriam
Abstract: This paper explores the linkages between migrant transnationality, locality, and the transformation of local government practices within the field of overseas development assistance (ODA). A growing literature critically analyses how migrants as development agents are embedded in, as well as challenge, local and transnational power hierarchies. This research field is not only centred on the dynamics in the countries of migrant origin but also includes the interaction between the social and institutional contexts in the receiving country and the transnational development practices of migrants. We explore these wider issues through an analysis of the overall trends in migrant access to ODA among Catalan local governments, which have dedicated a (small) part of their annual budget to ODA activities since the 1980s. We set up an original database with information from four consecutive comprehensive surveys of ODA practices of Catalan local governments between 1999 and 2008, each cohort representing more than 90% of the total Catalan population. Subsequently, we show that variation in migrant access to ODA funds across different local governments and migrant nationalities is related to both the size and diversity of municipalities and a range of institutional/political variables. These include the overall ODA spending of the local government, which party is in power, and the extent to which local governments pool their ODA resources within a regional development association for municipalities. In this way, the analysis contributes to our understanding of the potential of migration and migrant transnational practices to transform local institutional practices. Copyright © 2015 John Wiley & Sons, Ltd.